DON’T BREAK THE CHAIN: IMPORTANCE OF SUPPLY CHAIN MANAGEMENT IN THE OPERATING ROOM SETTING - Bilyk, Candis (Operating Room Nurses Association of Canada Journal, 2008)
Management of supplies within the operating room (OR) has considerable implications for decreasing healthcare costs while maintaining high-quality patient care. This area of healthcare therefore requires more monitoring by end-users including OR management, physicians, and nursing staff. This article is based on understanding supply chain management in the OR setting. Information provided throughout the article can be applied to small or large health care centers. It defines supply chain management and contains a brief overview of supply chain processes. It reviews the benefits of following these processes. The article also includes recommendations for improving the supply chain in the OR.